2019
DOI: 10.1093/brain/awz078
|View full text |Cite
|
Sign up to set email alerts
|

The debated toxic role of aggregated TDP-43 in amyotrophic lateral sclerosis: a resolution in sight?

Abstract: Cytoplasmic aggregation of TDP-43 is a hallmark of ALS, but its role in neurodegeneration remains controversial. After close examination of the current literature, Hergesheimer et al. conclude that TDP-43 aggregation is a major factor in neuronal death in ALS, with potential therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
145
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(150 citation statements)
references
References 204 publications
(252 reference statements)
1
145
4
Order By: Relevance
“…Our screening system will also be useful for identifying compounds that prevent cytoplasmic TDP-43 aggregation, which may contribute to a novel therapeutic strategy for ALS/FTLD. Although our screening system generally well recapitulated cytoplasmic TDP-43 aggregation in ALS/FTLD, our results were partially inconsistent with some previous reports on the pathology of inherited ALS [17,18]. Notably, we did not nd any evidence of TDP-43 aggregation in the neuronal cells expressing the inherited ALS/FTLD causative genes related to protein degradation (e.g., VCP, UBQLN2, SQSTM1, and TBK1), although the previous studies reported TDP-43 pathology in inherited ALS patients with these mutations [17].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our screening system will also be useful for identifying compounds that prevent cytoplasmic TDP-43 aggregation, which may contribute to a novel therapeutic strategy for ALS/FTLD. Although our screening system generally well recapitulated cytoplasmic TDP-43 aggregation in ALS/FTLD, our results were partially inconsistent with some previous reports on the pathology of inherited ALS [17,18]. Notably, we did not nd any evidence of TDP-43 aggregation in the neuronal cells expressing the inherited ALS/FTLD causative genes related to protein degradation (e.g., VCP, UBQLN2, SQSTM1, and TBK1), although the previous studies reported TDP-43 pathology in inherited ALS patients with these mutations [17].…”
Section: Discussioncontrasting
confidence: 99%
“…Although our screening system generally well recapitulated cytoplasmic TDP-43 aggregation in ALS/FTLD, our results were partially inconsistent with some previous reports on the pathology of inherited ALS [17,18]. Notably, we did not nd any evidence of TDP-43 aggregation in the neuronal cells expressing the inherited ALS/FTLD causative genes related to protein degradation (e.g., VCP, UBQLN2, SQSTM1, and TBK1), although the previous studies reported TDP-43 pathology in inherited ALS patients with these mutations [17]. Moreover, the co-localization of TDP-43 and the inherited ALS/FTLD causative gene products are still controversial even though TDP-43 pathology is widely observed in the patients with ALS.…”
Section: Discussioncontrasting
confidence: 99%
“…These results establish altFUS, rather than FUS, as the protein 199 responsible of the inhibition of autophagy. 200 Furthermore, altFUS interactome analysis suggested a role in the cellular stress response, which 201 is known to be altered in ALS with a TDP-43 cytoplasmic accumulation in 98 % of patients 41, 42 . In 202 FUS-linked ALS and some sALS cases, FUS cytoplasmic aggregates or mislocalization are also 203 observed [43][44][45] .…”
Section: As Cells Transfected With Fus or Fus-192mentioning
confidence: 99%
“…Our work shows that FUS synonymous 328 mutations found in patients cluster on altFUS genomic locus. We tested 4 of these mutations, 329 synonymous for the FUS protein and missense for the altFUS protein, and we found that each of 330 them potentiated TDP-43 cytoplasmic aggregation, a pathological hallmark of ALS 42 Throughout the neural conversion and patterning phase (D0-18) the neuroepithelial layer was 419 enzymatically dissociated twice (at D4-5 and D10-12) using dispase (GIBCO, 1 mg ml-1). 420…”
mentioning
confidence: 99%
“…It remains controversial whether TDP-43 aggregation is the principal cause of the motor neuronal degeneration observed in ALS patients, but recent studies shed a light into the key role of TDP-43 aggregates in causing the observed neurodegeneration. Further, TDP-43 aggregates are present in patients with and without any mutations in the TDP-43 encoding gene, TARDPB, and in patients with mutations in other genes involved in ALS pathology, like SOD-1 and C9orf72 (reviewed by [3]). Similar pathophysiological mechanisms are described for both genetic and sporadic ALS patients, and as 97% of ALS patients present TDP-43 aggregation, it is plausible to suggest a link between TDP-43 and some of the pathogenic mechanisms [4,5].…”
Section: Introductionmentioning
confidence: 99%